The Transformation of the Mother-Daughter Relationship in Amy Tan’s The Joy Luck Club and The Bonesetter’s Daughter - Kordel, Patrycja (Analyses/Rereadings/Theories: A Journal Devoted to Literature, Film and Theatre, 2014)
The mother/daughter bond is the central subject of Amy Tan’s two powerful books, The Joy Luck Club and The Bonesetter’s Daughter. Tensions that arise in the novels between a Chinese mother and her Chinese-American daughter are often described by the critics as being the result of two important factors. One is based on the misunderstandings caused by the generational gap, while the other comes from the cultural gap. For a Chinese-born mother the American reality instigates various confusions, as she still views her life with the eyes of her traditional Chinese upbringing. On the other hand, her daughter lacks any profound knowledge about her Chinese ethnicity, which makes her unable to recognize the influences of her mother’s Chinese past over their relationship. But in her novels Tan portrays also the relationship between the Chinese immigrant mother and her mother in China. Their relationship, which grew up exclusively on the grounds of the Chinese culture, is characterized by empathy and appreciation. In this paper I am going to discuss the change that occurred to the mother-daughter relationship after it has been replanted into a different cultural context. The line of argument will reveal in what ways the mother-daughter relationship underwent a significant transformation.